Glucose Uptake in Prochlorococcus: Diversity of Kinetics and Effects on the Metabolism - Muñoz-Marín, María del Carmen; Gómez-Baena, Guadalupe; Díez, Jesús; Beynon, Robert J.; González-Ballester, David; Zubkov, Mikhail V.; García-Fernández, José M. (Frontiers in Microbiology, 2017)
We have previously shown that Prochlorococcus sp. SS120 strain takes up glucose by using a multiphasic transporter encoded by the Pro1404 gene. Here we studied the glucose uptake kinetics in multiple Prochlorococcus strains from different ecotypes, observing diverse values for the Ks constants (15 – 126.60 nM) and the uptake rates (0.48 – 6.36 pmol min-1 mg prot-1). Multiphasic kinetics was observed in all studied strains, except for TAK9803-2. Pro1404 gene expression studies during the 21st Atlantic Meridional Transect cruise showed positive correlation with glucose concentrations in the ocean. This suggests that the Pro1404 transporter has been subjected to diversification along the Prochlorococcus evolution, in a process probably driven by the glucose availabilities at the different niches it inhabits. The glucose uptake mechanism seems to be a primary transporter. Glucose addition induced detectable transcriptomic and proteomic changes in Prochlorococcus SS120, but photosynthetic efficiency was unaffected. Our studies indicate that glucose is actively taken up by Prochlorococcus, but its uptake does not significantly alter the trophic ways of this cyanobacterium, which continues performing photosynthesis. Therefore Prochlorococcus seems to remain acting as a fundamentally phototrophic organism, capable of using glucose as an extra resource of carbon and energy when available in the environment.